2019
DOI: 10.1093/aob/mcz009
|View full text |Cite
|
Sign up to set email alerts
|

Novel Miscanthus genotypes selected for different drought tolerance phenotypes show enhanced tolerance across combinations of salinity and drought treatments

Abstract: Background and AimsWater deficit and salinity stresses are often experienced by plants concurrently; however, knowledge is limited about the effects of combined salinity and water deficit stress in plants, and especially in C4 bioenergy crops. Here we aim to understand how diverse drought tolerance traits may deliver tolerance to combinations of drought and salinity in C4 crops, and identify key traits that influence the productivity and biomass composition of novel Miscanthus genotypes under such conditions.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 106 publications
(128 reference statements)
8
29
1
Order By: Relevance
“…However, for all plants trajectories of stem growth, leaf expansion, and tillering (stem number) curves were significantly affected by the applied treatment. Several studies, both in greenhouse and field conditions, reported that stem elongation and leaf area were significantly affected in M. × giganteus and M. sacchariflorus but not in M. sinensis [17,[25][26][27]29,34,57]. In the present study, the morphological trait changes under applied drought conditions were in line with previous findings for pots experiments [25,28,29,34,58].…”
Section: High Yielding Miscanthus Genotypes Demonstrated a Diversity supporting
confidence: 92%
See 1 more Smart Citation
“…However, for all plants trajectories of stem growth, leaf expansion, and tillering (stem number) curves were significantly affected by the applied treatment. Several studies, both in greenhouse and field conditions, reported that stem elongation and leaf area were significantly affected in M. × giganteus and M. sacchariflorus but not in M. sinensis [17,[25][26][27]29,34,57]. In the present study, the morphological trait changes under applied drought conditions were in line with previous findings for pots experiments [25,28,29,34,58].…”
Section: High Yielding Miscanthus Genotypes Demonstrated a Diversity supporting
confidence: 92%
“…To test this, a large number of phenotypic traits associated with yield accumulation [17][18][19][20], and complex traits such as seasonal duration and harvestable yield [21][22][23] have been measured in diverse miscanthus populations. A number of studies have examined responses to, and genotypic variation in traits associated with, drought [24][25][26][27][28][29]. However, drought resistance in undomesticated miscanthus is the result of natural evolution and may not necessarily favour growth under stress but rather survival.…”
Section: Introductionmentioning
confidence: 99%
“…Different miscanthus species vary in tolerance to various physical factors. According to physiological measurements (F v /F m ), Mxg displayed the highest vitality under cold (together with M. sacchariflorus) [15] and drought (together with M. sinensis) [16] stress among other miscanthus species. Mxg physiological response was more sensitive to salinity and combination of salinity and drought than M. sinensis but more tolerant than M. floridulus [16].…”
Section: Introductionmentioning
confidence: 99%
“…According to physiological measurements (F v /F m ), Mxg displayed the highest vitality under cold (together with M. sacchariflorus) [15] and drought (together with M. sinensis) [16] stress among other miscanthus species. Mxg physiological response was more sensitive to salinity and combination of salinity and drought than M. sinensis but more tolerant than M. floridulus [16]. Also novel hybrids were developed, which exhibited higher yields under drought, salinity and cold stress conditions than Mxg [17].…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus sinensis exhibits salt spray tolerance growing in coastal landscapes as ornamental grass [ 5 , 6 ], with salt concentrations higher than 10 dS m −1 NaCl reducing the yield by over 50% [ 7 ]. The genetic diversity of salt tolerance to combinations of salinity and drought conditions [ 8 ] and single salt stress in Miscanthus have been recently documented [ 9 , 10 , 11 ]. Nevertheless, studies of salt tolerance mechanisms in Miscanthus have focused on the morphophysiological and biochemical [ 7 , 8 , 10 , 11 , 12 , 13 ] and transcriptional [ 14 ] responses.…”
Section: Introductionmentioning
confidence: 99%